2014
DOI: 10.1007/s00418-014-1257-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the long-chain fatty acid receptor GPR120 in the gonadotropes of the mouse anterior pituitary gland

Abstract: G-protein-coupled receptor 120 (GPR120) has been known to be a receptor of long-chain fatty acids. Here, we investigated GPR120 expression in the mouse pituitary gland via real-time PCR, in situ hybridization, and immunohistochemistry. GPR120 mRNA was abundantly expressed in the pituitary gland of ad-lib fed animals. In situ hybridization and immunohistochemistry revealed GPR120 expression in the gonadotropes of the anterior pituitary gland, but not in thyrotropes, somatotropes, lactotropes, corticotropes, mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Expression of FFA4, but not FFA1 transcript has been shown in rat pituitary gland and pituitary primary cultures [69], while the immortalized LβT2 mouse gonadotrope cell line was shown to express both receptors [69]. Expression of FFA4 was also investigated in the intact mouse pituitary gland, where it was shown to be densely expressed on gonadotropes, but not thyrotropes, somatotropes, lactotropes, corticotropes, melanotropes, or within the posterior pituitary gland [70]. Colocalization of FFA4 with luteinizing and follicle stimulating hormones within the gonadotropes suggested that the receptor could play a role in synthesis and/or GnRH-dependent release of the gonadotrophs [70].…”
Section: Ffa4 Expression and Tissue-specific Physiological Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of FFA4, but not FFA1 transcript has been shown in rat pituitary gland and pituitary primary cultures [69], while the immortalized LβT2 mouse gonadotrope cell line was shown to express both receptors [69]. Expression of FFA4 was also investigated in the intact mouse pituitary gland, where it was shown to be densely expressed on gonadotropes, but not thyrotropes, somatotropes, lactotropes, corticotropes, melanotropes, or within the posterior pituitary gland [70]. Colocalization of FFA4 with luteinizing and follicle stimulating hormones within the gonadotropes suggested that the receptor could play a role in synthesis and/or GnRH-dependent release of the gonadotrophs [70].…”
Section: Ffa4 Expression and Tissue-specific Physiological Functionsmentioning
confidence: 99%
“…Expression of FFA4 was also investigated in the intact mouse pituitary gland, where it was shown to be densely expressed on gonadotropes, but not thyrotropes, somatotropes, lactotropes, corticotropes, melanotropes, or within the posterior pituitary gland [70]. Colocalization of FFA4 with luteinizing and follicle stimulating hormones within the gonadotropes suggested that the receptor could play a role in synthesis and/or GnRH-dependent release of the gonadotrophs [70]. However, Garrel and colleagues showed that neither GW9508 nor the unsaturated fatty acid linoleate could induce LH secretion in LβT2 cells, implying that FFA1 and FFA4 are not involved in gonadotroph release [69].…”
Section: Ffa4 Expression and Tissue-specific Physiological Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues were fixed and processed as previously described [4,13]. First, mice were anesthetized using a ketamine/xylazine mixture (8.75 mg ketamine and 1.25 mg xylazine/100 g BW), and then perfused with 0.05 M phosphate-buffered saline (PBS), followed by 4% paraformaldehyde in 0.05 M phosphate buffer (PB).…”
Section: Tissue Preparation For Immunohistochemistrymentioning
confidence: 99%
“…However, the long-chain fatty acid receptor agonist GW9508 did not affect LH secretion [5] or the transcription of the gonadotropin subunit genes [6] in an LβT2 gonadotropic cell line. Nevertheless, fasting induced an increase in GPR120 mRNA expression in mouse gonadotrophs [4] and free fatty acids (FFAs) directly suppressed Fshb mRNA expression in the LβT2 gonadotropic cell line [7], suggesting that GPR120 could serve as a sensor for the detection of serum fatty acid levels in pituitary gonadotrophs.…”
mentioning
confidence: 99%